2015
DOI: 10.1007/978-3-319-06590-8_86
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Optimization of Hydrodynamic Journal Bearings with Validated Simulations and Artificial Intelligence Tools

Abstract: The scope of this work is to mathematically optimize the choice of geometrical parameters of a hydrodynamic journal bearing to maximize its performance. Despite the fact that several works have investigated methods to predict the optimal shape of this family of sliding bearings, significant opportunities remain to improve the efficiency of the algorithm through the use of validated computational fluid dynamics and intelligent stochastic algorithms to find the function's maximum and minimum. This work presents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Later on in another study by them in 2016, 9 a steady-state performance analysis of two-lobe oil journal bearing was also optimized by considering the minimization of friction variable, maximization of non-dimensional load-carrying capacity, and flow rate as objective functions. In 2015, an Artificial Bee Colony algorithm for finding the optimal performance of fixed pad hydrodynamic journal bearings was proposed by Gorasso et al 10 The objective functions were the minimization of the aggregates mass flow, power loss, maximum pressure, temperature rise, and minimum lubricant film thickness. A three-dimensional computational fluid dynamics model on commercial software Ansys Fluent was also employed to calculate the performance of the bearing.…”
Section: Introductionmentioning
confidence: 99%
“…Later on in another study by them in 2016, 9 a steady-state performance analysis of two-lobe oil journal bearing was also optimized by considering the minimization of friction variable, maximization of non-dimensional load-carrying capacity, and flow rate as objective functions. In 2015, an Artificial Bee Colony algorithm for finding the optimal performance of fixed pad hydrodynamic journal bearings was proposed by Gorasso et al 10 The objective functions were the minimization of the aggregates mass flow, power loss, maximum pressure, temperature rise, and minimum lubricant film thickness. A three-dimensional computational fluid dynamics model on commercial software Ansys Fluent was also employed to calculate the performance of the bearing.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, they also published a new study 9 about the optimization of a two lobe oil elliptical journal bearing by considering the same objective functions and optimization algorithm. In 2015, Gorasso et al 10 found the optimal performance of fixed pad hydrodynamic journal bearings by minimization of the aggregates mass flow, power loss, maximum pressure, temperature rise, and minimum lubricant film thickness. To calculate the performance of the bearing, they utilized a three-dimensional computational fluid dynamics model using the commercial software Ansys Fluent.…”
Section: Introductionmentioning
confidence: 99%